O conceito de religião em Kant e o problema teleológico do argumento moral - Pereira, Davi Gadelha (2016)
The title of the research suggests two specially moments, namely, first of all, that will be given focus to a overview of what comes to be the concept of religion in Kant, in order to, clarify the exact moment in which to determine, in his philosophy, passage of morality to religion. However, we seek to explain briefly and as far as possible - considering the chronogram of the research – the architectural who philosopher studied developed in order to explain philosophically the concept of religion from morality, in his writings about these respective terms. In the second moment, we approach, specifically, the teleological problem faced by the Kantian moral argument for the existence of God. Therefore, the problematization begins with preliminary considerations on religion and consolidated from the analysis of the second part of the propose theme, which refers to the moral argument (fundamental purpose of all critical and especially of the second) and the teleological question, in other words, of the ultimate finality of every rational causality. Now, as the concept postulated a supreme lawgiver can harmonize to final purpose of the moral law and the laws of nature in a transcendental purely process? Indeed, the exhaustive task of the Kant was, therefore, to reconcile the teleology of nature with the teleology of freedom promoting the bridge was missing between theoretical reason and its extension, the practical reason. Thus, his critical philosophy consisted in linking the purpose moral with the purpose of the nature in teleological reflective judgment. Without it can be determined the nature of God in theoretical field of reason, its existence can be naturally accepted as a concept that embraces itself all conformity to the purposes of reason, both theoretical and practical. These foundamentals are put from the critical works, while it comes to an ethical-religious valuation derived the normatives of reason, which aligns with the exaltation of the philosopher to moral law taking as representing freedom of duty.